The Relationship Between Perceived Stress, State-Trait Anxiety, and Sleep Quality Among University Graduates in China During the COVID-19 Pandemic - Liu, Bailong; Qiao, Ke; Lu, Youfeng (Frontiers in Psychology, 2021)
Investigate the relationship among perceived stress, state-trait anxiety and sleep quality of graduating students, to provide a reference for improving their psychological status and attitude adjustment of job-searching during COVID-19 pandemic. The research was conducted in a descriptive and cross-sectional online survey between May 2020 and August 2020 at 11 universities of Shaanxi Province. The data was collected from 1200 participants by using the personal information form prepared by the researchers in line with the literature, the Perceived Stress Scale (PSS), the State-Trait Anxiety Inventory (STAI), and the Pittsburgh Sleep Quality Index (PSQI). Among the surveyed participants, 47.67% were female, and 10.92% were medical students. The mean perceived stress, state anxiety, trait anxiety, and sleep quality were moderate and found as 31.4±6.69, 46.67±5.80, 49.45±5.54, and 5.94±2.47, respectively. The detection rates of state anxiety and trait anxiety were 48.63% and 49.50% respectively. There was no significant difference in the detection rate of state anxiety and trait anxiety among different genders and majors (P>0.05). The detection rate of state anxiety and trait anxiety of rural family students was higher than that of urban family students (P<0.01). The score on the Pittsburgh Sleep Quality Index was positively associated with the scores on the perceived stress, state anxiety, trait anxiety scales (p<0.001 for each model). Sleep Quality was associated with increased perceived stress, state anxiety and trait anxiety among graduating students in China. Additional studies on the relationship between sleep quality and mental health problems, as well as its potential mechanism, are warranted.